Developing Arabic Speaking Skills through Muhadatsah: A Case Study at Al-Marhamah Puteri Islamic Boarding School - M. Anwar; Noor, Fatwiah; Elsa Maylinda; Ahmed, Brakat Mohammed (Arabiyatuna: Jurnal Bahasa Arab, 2025)
The Muhadatsah program represents an Arabic language learning method that emphasizes speaking practice. While numerous studies have explored language learning theories, empirical evidence on the effectiveness of the Muhadatsah program in enhancing speaking proficiency, particularly within the Indonesian context, remains limited. This study aimed to examine the implementation of the Muhadatsah program as a strategy for developing speaking skills among female students (santriwati) at Al-Marhamah Puteri Islamic Boarding School, Sampit, Central Kalimantan. Employing a qualitative case study approach, data were collected through observation, interviews, and documentation, and subsequently analyzed inductively. The findings indicate that the Muhadatsah program was effectively implemented and followed established procedures, contributing to the improvement of students’ speaking skills, although challenges related to vocabulary acquisition persisted. One solution introduced was the compulsory submission of new vocabulary outside program hours. This study contributes to filling the gap in the literature on the practical implementation of the Muhadatsah program within the Islamic boarding school context.